2018
DOI: 10.1177/0361198118801338
|View full text |Cite
|
Sign up to set email alerts
|

Getting Business People on the Coach: A Stated Preference Experiment for Intercity Long Distance Coach Travel

Abstract: From the middle of the 1990s, the traditional coach industry in Western Europe has been in decline. However, recent regulatory changes have created new opportunities in the sector of scheduled intercity services, resulting in fast growth of both coach lines and passengers traveling on these lines. Until now, operators have persuaded a public consisting mainly of students and people traveling for leisure purposes. In this paper we analyze whether business travelers could also be an interesting target group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…(and the lowest). Furthermore, the likelihood of the none-of-these option could be estimated (Hauber et al, 2016;Hosmer & Lemeshow, 2000;Lannoo et al, 2018;Train, 2009). The third reason was that the model allowed the inclusion of the none-of-these option.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(and the lowest). Furthermore, the likelihood of the none-of-these option could be estimated (Hauber et al, 2016;Hosmer & Lemeshow, 2000;Lannoo et al, 2018;Train, 2009). The third reason was that the model allowed the inclusion of the none-of-these option.…”
Section: Methodsmentioning
confidence: 99%
“…The third reason was that the model allowed the inclusion of the none-of-these option. This made it easier to estimate the coefficients and to give a better predictive fit than not including it or using a nested logit model (Haaijer et al, 2001;Lannoo et al, 2018;Van Acker et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…For long-distance travel-based on work by Limtanakool et al [18] for the car, Creemers et al [10] for light rail, Vanoutrive et al [34] for rail, Lannoo et al [16] and Van Acker et al [31] for bus/coach travel, Aparicio [1] for car and air travel, and Lepage [17] for rail and air travel-three common mode determining variables are important: (1) travel time, (2) travel cost, and (3) overall comfort/convenience. In most cases, the longer the travel time, the less likely this mode will be chosen.…”
Section: Factors Influencing Long Distance Modal Choicementioning
confidence: 99%
“…Toilets on-board coaches or trains are indeed often poorly maintained. In their study of business travellers, Lannoo et al (2018) found that other comfort attributes such as ample leg space, on-board Wi-Fi and the entertainment system also play a role. The effect, however, depends on the frequency of travelling.…”
Section: The (Potential) Role Of Coach Transport In Long-distance Travelmentioning
confidence: 99%